You are on page 1of 8

## Bacterius — Math Help Forum

May 19, 2010

Abstract

Contents
1 Definition 2

2 Algebraically 2
2.1 Polynomial representation . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 2
2.2 Solving for x . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 2
2.2.1 Factorizing the equation . . . . . . . . . . . . . . . . . . . . . . . . . . . . 2
2.2.2 Using the quadratic formula . . . . . . . . . . . . . . . . . . . . . . . . . . 3

3 Graphically 5
3.1 Representation of a quadratic equation . . . . . . . . . . . . . . . . . . . . . . . . 5
3.2 Completing the square . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 6
3.3 Completing the square – the lazy way . . . . . . . . . . . . . . . . . . . . . . . . 7
3.4 Graphical properties of the parabola . . . . . . . . . . . . . . . . . . . . . . . . . 8

1
1 Definition
The so-called quadratic equation is a widely used mathematical concept. It is immensely powerful
in a range of areas, from the flight time of a bird to advanced projectile motion, and is easy to use
when understood. Due to its notoriety, many tools have been designed to facilitate the analysis

2 Algebraically
2.1 Polynomial representation
Mathematically speaking, a quadratic equation is a polynomial equation of degree two. That is,
all quadratic equations can be defined by three parameters a, b, c ∈ R, with a 6= 0, as follows :

ax2 + bx + c = 0

## 2.2 Solving for x

One recurring question about quadratic equations is how to actually solve them. There are two
ways of solving a quadratic equation :

The first method does not always work (we will see why), while the second is general and will
succeed in solving the equation for any values of a, b and c (even those which yield an equation
that doesn’t have real solutions). This list does not include “completing the square” as it is
essentially the same as using the quadratic formula.

## 2.2.1 Factorizing the equation

When facing the polynomial ax2 + bx + c = 0, it is desirable to be able to “break” the left hand
side into more tractable (easier) parts that multiply together to give the original expression.
This is because since the right hand side is zero, and that multiplication has a special property
regarding zeroes, it is possible to treat each little part independently to solve the equation. For
instance, consider x2 + 2x − 3 = 0. This factorizes as (x − 1)(x + 3) = 0, and this can be checked
by expanding. Now, this expression means – again because the right hand side is zero, otherwise
it fails – that either x − 1 = 0, either x + 3 = 0, which gives the two solutions to the equation,
x = 1 and x = −3.
Now, is there a general way to factorize quadratic equations ? The answer is no. Not only
there are infinitely many equations that can’t be factorized using only integer or fractions, or
even in real numbers, but factorization in general is believed to be a hard problem that cannot
be done instantly. Hopefully there are some tricks that can be carried out for quadratic equation
factorization to be easier. We can distinguish two cases : when a = 1, and where a 6= 1. Let us
analyze the first case, so we have the equation :

x2 + bx + c = 0

2
How can we factorize this ? Remember what we want is something in the form (x−m)(x−n) = 0.
Maybe it would be better to expand this instead of factorizing the original equation :
(x − m)(x − n) = 0
2
x − (m + n)x + mn = 0
Comparing this with our original equation, we see that b = −(m + n) and c = mn. The smart
among you might wonder, these two equations can be simultaneously solved so why bother ? Yes,
but solving them requires to solve another quadratic equation, which is what we are actually
trying to do. So the only alternative is to basically guess and check. Once you found two
numbers m, n that multiply together to give c, and add together to give b, then you know that
x2 + bx + c = (x − m)(x − n). Then, the solutions to the equation are simply :
x=m and x=n
Doing this a lot, you will soon be able to mentally factorize most quadratic equations quickly.
Now what if a 6= 1 ? This is harder, because we have to factorize the full equation :
ax2 + bx + c = 0
We now want something else, in the form (px − m)(qx − n) = 0 (the coefficients in front of
the x are necessary to obtain ax2 ). So let’s expand this :
(px − m)(qx − n) = 0
2
pqx − x(pn + qm) + mn = 0
Now you need to find two numbers that multiply to a, two other numbers that multiply to c,
and check that those four numbers satisfy pn + qm = b. This is not the most optimized method,
but better ones will not be dwelled upon in this paper as the quadratic formula is much more
useful and simple to use.

As to conclude on factorizing quadratic equations, bear in mind that there are some equations
that simply cannot be solved this way – typically, you won’t be able to find two numbers that
multiply to c and add to b for instance, because these just don’t exist.

## 2.2.2 Using the quadratic formula

So what do we do when we hopelessly realize our equation can’t be factorized using the previous
method (or are too lazy to bother trying) ? We use a formula called the quadratic formula, which
quickly gives the two solutions for x. Without further ado :

−b ± b2 − 4ac
If ax2 + bx + c = 0, then x =
2a
There are a couple of issues with this formula, though. At some point you are surely going
to get a “Math error” on your calculator, and this is because the value of b2 − 4ac will be
negative, and the square root of a negative number doesn’t exist. To avoid this, mathematicians
have designed a new tool, called the discriminant, which actually is the quantity b2 − 4ac. It
establishes a relationship between the number of real solutions a quadratic solution has, and the
value of the discriminant, as follows :

 < 0 No real solutions
∆ = b2 − 4ac = 0 One real solution
> 0 Two real solutions

3
We may add another line : if ∆ is a perfect square, the solutions will be rational (the proof
is left as an exercise to the reader). For more explanation on why this is (apart from the fact
that taking the square root of a negative real number is not possible, and that ∆ = 0 yields a
repeated root), you can read though the proof in the “Graphical” section. It does not require
knowledge on how to derive the quadratic formula.

Anyway, this formula always works (it can be used to find complex roots, which you will
probably find about soon) and is easy to use, apart that it is easy to make a sign error, especially
in the discriminant. This is handy, and this is how it was discovered (follow the steps) :

ax2 + bx + c = 0

b c
x2 + x + = 0
a a

 2  2
b b b c
x2 + x + − + =0
a 2a 2a a

 2  2
b b c
x+ = −
2a 2a a

s 2
b b c
x+ =± −
2a 2a a

r
b b2 − 4ac
x+ =±
2a 4a2

b b2 − 4ac
x+ =± √
2a 4a2

−b ± b2 − 4ac
x=
2a

## In conclusion, unless the factorization of a quadratic equation is quite obvious, it is often

faster to use the quadratic formula. Note that a factorization of the quadratic equation can be
trivially derived from this formula. Indeed :
√ ! √ !
2 −b − b2 − 4ac −b + b2 − 4ac
ax + bx + c = x − x− =0
2a 2a

4
3 Graphically
3.1 Representation of a quadratic equation
Graphically, by plotting the values of y(x) = ax2 + bx + c against x, all quadratic equations
always take the shape of a parabola. This is due to the squared x value : x2 is not proportional
to x, so the graph cannot possibly be a line. As x2 = (−x)2 , the shape of the curve will be
symmetrical. And, to finish, x2 will increase faster than x for |x| > 1, therefore leading to an
ever-increasing slope. The three parameters a, b and c give information on how the parabola will
look like. For instance, if a > 0, then the parabola will go down, then up, much like this :

Here the parabola is defined by a = 1, b = 1, and c = 1. When a < 0, then the parabola will
be reversed : it will go up, then down. This is commonly called the direction of the parabola,
and is solely parameterized by a (b and c are not involved in the direction nor the slope of the
parabola). Also, the absolute value of a gives information on the slope of the parabola : greater
means steeper. As an illustration of this statement, the following graphs were plotted together :

5
The red parabola is defined by a = 2, the blue one by a = 1 and the green one by a = 0.5.
Note how the slope of the parabola gets steeper as a increases. This is also valid for negative
values of a : the slope will be identical, the parabola will simply be reversed.

There is a problem, though : the values of b and c are not of much use when considering the
graphical representation of a quadratic equation. This is why another tool exists, which is called
the vertex form. It is another equation which is, while being equivalent to the original quadratic
equation, much more intuitive when looking at parabolas, and takes the general form of :

y = a(x − h)2 + k

In this case, a still gives information on the direction and slope of the parabola (actually, it is
identical to the a of the first equation), h gives the horizontal displacement of the parabola, and
k gives the vertical displacement of the parabola. Indeed, if the graph of any quadratic equation
is compared to the “basic” equation y = x2 , one can see that it is not that much different : the
only difference resides in the slope and direction of the parabola and the position of the vertex.
With the new equation, the vertex is simply located at the point (h, k). For instance, using the
equation y = (x − 2)2 + 1 with a = 1, h = 2, k = 1, we graph this :

## 3.2 Completing the square

As expected, the vertex of the parabola does lie at the point (2, 1). But what do we do when
the quadratic is not given in vertex form ? We will have to transform the given equation,
y = ax2 + bx + c, into vertex form y = a(x − h)2 + k. This is a fairly simple process, often called
completing the square. The goal of this algebraic manipulation is to arrange terms in such a way
that one is left with a square expression involving x, and a “leftover” that will become k. For
instance, say we want to convert y = 3x2 + 6x − 1 to vertex form. First, write the equation :

y = 3x2 + 6x − 1

## Then, divide everything by a = 3. So :

y 1
= x2 + 2x −
3 3
Remember the identity (m + n)2 = m2 + 2mn + n2 ? This is the one which will allow us to
achieve this process. Here, if we assume that m = x, we know that n = 1 (because we see

6
that 2mn = 2x), which nearly fits the original equation. Indeed, the identity requires that we
have n2 = 12 = 1 at the end, but we have −1 3 . So how can we do ? We can simply state that
−1 4
3 = 1 − 3 . This may seem very pointless at first, but it allows us to complete the square :

y 4
= x2 + 2x + 1 −
3 3
Now, using the identity on all but the last term :
y 4
= (x + 1)2 −
3 3
Then, multiply everything by a = 3 :

y = 3(x + 1)2 − 4

And we have the vertex form of the equation, giving us all the precious information we needed
m = x is necessary because vertex form does not allow any coefficient directly in front of the x.

## 3.3 Completing the square – the lazy way

There is a way to define h and k with regard to b and c, to go even faster. Indeed, consider the
quadratic equation y = ax2 + bx + c. Much like previously, we divide everything by a :
y b c
= x2 + x +
a a a
b b
Then, as before, ax = 2mn, and since m = x, we must have n = 2a . So we do as follows :
 2  2
y b b b c
= x2 + x + − +
a a 2a 2a a

This might feel like cheating but it is a valid way of doing it . . . Now that we have our square :
 2  2
y b b c
= x+ − +
a 2a 2a a

## Now rearranging a bit all of this, and multiplying by a :

2
b2

y b 4ac
= x+ − 2
+ 2
a 2a 4a 4a

2
b2 − 4ac

y b
= x+ −
a 2a 4a2

2
b2 − 4ac

b
y =a x+ −
2a 4a

7
This is the vertex form. So, we can conclude by giving the relationships :

−b b2 − 4ac
h= and k=−
2a 4a

Note that you can spot the discriminant of the equation here – and more importantly, you can
finally see why it actually succeeds in telling us the number of real roots the equation has. Let
∆ = b2 − 4ac, and assume that a is positive, then if ∆ = 0, k = 0, so the equation becomes
y = a(x − h)2 which must only touch the x-axis in one x value. If ∆ > 0, then a(x − h)2 is

positive and − 4a is negative, so the equation will have negative values (the parabola will cross

the x-axis in two distinct points). Finally, if ∆ < 0, then a(x − h)2 is still positive but − 4a
becomes positive, so their sum will remain positive, therefore the parabola will never touch the
x-axis (and thus no real solutions). If a is negative, a similar argument can be used, with minor
modifications. This leads to the same conclusion found using direct algebra :

 < 0 No real solutions : parabola does not touch the x-axis
∆ = b2 − 4ac = 0 One real solution : parabola is tangent to x-axis
> 0 Two real solutions : parabola does cross the x-axis